Plasma GFAP and NfL associate with cerebral glucose metabolism in putative brain-first and body-first Parkinson’s disease subtypes - Shiyu Li; Fangyang Jiao; Xiuyuan Li; Zhiheng Xu; Tianyu Hu; Xiaoniu Liang; Jianjun Wu; Jian Wang; Chuantao Zuo; Yilin Tang (npj Parkinson's Disease)
Abstract The recently proposed body-first and brain-first subtypes are classified based on the initial localization of α-synuclein inclusions. This study investigated plasma biomarkers and cerebral glucose metabolism characteristics in putative brain-first and body-first subtypes in PD subjects. PD patients without possible RBD (PDpRBD–) (n = 58) and with possible RBD symptoms discovered before motor symptoms (PDpRBD+) (n = 43) were recruited. Single-molecule array (SimoA) was used for measuring plasma biomarkers, including glial fibrillary acidic protein (GFAP), neurofilament light chain (NfL), Tau and phosphorylated-tau 181 (pTau-181). All participants underwent 18F-fluorodeoxyglucose (FDG) PET scans. Compared to PDpRBD– patients, PDpRBD+ patients exhibited significantly increased plasma GFAP levels and reduced 18F-FDG uptake in cortical regions. Notably, plasma GFAP and NfL levels correlated with cerebral glucose metabolism in PDpRBD– patients. Our study identified the association between plasma GFAP and NfL levels and cerebral glucose metabolism in PDpRBD– patients. Further large-scale longitudinal studies are required.